2022
DOI: 10.14218/jcth.2021.00306
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Dysfunction-associated Fatty Liver Disease is Associated with Greater Impairment of Lung Function than Nonalcoholic Fatty Liver Disease

Abstract: Background and Aims:We compared lung function parameters in nonalcoholic fatty liver disease (NAFLD) and metabolic dysfunction-associated fatty liver disease (MAFLD), and examined the association between lung function parameters and fibrosis severity in MAFLD. Meth-ods: In this cross-sectional study, we randomly recruited 2,543 middle-aged individuals from 25 communities across four cities in China during 2016 and 2020. All participants received a health check-up including measurement of anthropometric paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…the leading cause of death in people with NAFLD), certain types of extra-hepatic cancers, chronic pulmonary and renal diseases. [23][24][25][26][27][28] Despite intensive research, there is still no drug to date that has been approved for the treatment of NAFLD or NASH. Lifestyle modifications, which include hypocaloric diet and physical activity to achieve weight loss, are the cornerstone of treatment for NAFLD and NASH.…”
Section: Introductionmentioning
confidence: 99%
“…the leading cause of death in people with NAFLD), certain types of extra-hepatic cancers, chronic pulmonary and renal diseases. [23][24][25][26][27][28] Despite intensive research, there is still no drug to date that has been approved for the treatment of NAFLD or NASH. Lifestyle modifications, which include hypocaloric diet and physical activity to achieve weight loss, are the cornerstone of treatment for NAFLD and NASH.…”
Section: Introductionmentioning
confidence: 99%
“…However, these do not necessarily need to be ruled out and reported in MAFLD diagnosis. MAFLD, on the other hand, probably offers the advantage of more accurately identifying the risk of target organ dysfunction, namely, progressive liver disease [ 120 ] , diabetes and chronic kidney disease [ 121 ] , atherosclerosis [ 122 ] , more severely impaired lung function [ 123 ] , colon cancer [ 124 ] , both intrahepatic and extrahepatic events [ 125 ] , and mortality [ 126 ] , although the last outcome is controversial [ 127 ] .…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence indicating that the extent of lung impairment is higher in MAFLD than in NAFLD. On analyzing 2543 middle-aged individuals recruited from 25 communities across four cities in China, Miao et al 52 found that patients with MAFLD were characterized by significantly lower forced vital capacity (88.27 ± 17.60% versus 90.82 ± 16.85%, p < 0.05) and one second forced expiratory volume (79.89 ± 17.34 versus 83.02 ± 16.66%, p < 0.05) than those with NAFLD.…”
Section: Natural Historymentioning
confidence: 99%
“…51 There is also evidence indicating that the extent of lung impairment is higher in MAFLD than in NAFLD. On analyzing 2543 middle-aged individuals recruited from 25 communities across four cities in China, Miao et al 52 Finally, colorectal malignancies are prevalent in patients with MAFLD. 53 Interestingly, their burden has been associated with the severity of both MAFLD and NAFLD.…”
Section: Natural Historymentioning
confidence: 99%